THE EFFECT OF INTERNSHIPS AND WORK MOTIVATION ON COLLEGE STUDENTS' WORK READINESS - Setiawan, Ryan Pradipta; Christian Wiradendi Wolor; Febriantina, Susan (Neraca: Jurnal Ekonomi, Manajemen dan Akuntansi, 2023)
Work readiness is one of the main assets that students must have before entering the world of work. The purpose of this study was to determine the effect of internships and work motivation on the work readiness of students of the Economics and Administration Education Study Program at State University of Jakarta. The research method that researchers use in this study is a survey method with a quantitative approach. The population in this study were all active students of the Economics and Administration Study Program at State University of Jakarta, totaling 1,634 students and the affordable population was 318 students. The sampling technique used proportionate stratified random sampling using the Slovin formula with a margin of error of 10% so that the sample in this study amounted to 76 students. The data analysis technique used in this study uses SmartPLS version 4.0 software. Furthermore, the data analysis techniques that researchers use in this study consist of outer model analysis, inner model analysis, and direct effect hypothesis testing. The results of the study indicate that there is a positive and significant direct effect together between Internships and Work Motivation on student’ Work readiness.